Elaboración de un folleto fotográfico de los valores culturales y ancestrales del pueblo kichwa de alpamalag- cantón pujilí para la difusión en la Unidad Educativa Miguel de Cervantes Perteneciente a la localidad, en el periódo 2014-2015 - Palomo Mancera, Martha Susana (2015)
Cotopaxi Province has seven cantons with big ancient and cultural wealth. At current, a lot of people have been devaluing each one of the manifestations. This resulted next investigation topic: “A PHOTOGRAPHIC BOOKLET DEVELOPMENT ABOUT CULTURAL VALUES AND ANCIENT VILLAGE OF ALPAMALAG KICHWA - PUJILÍ CANTON FOR BROADCASTING AT “MIGUEL DE CERVANTES” EDUCATIONAL UNIT RELATED TO THE LOCALITY, DURING 2014-2015”. The research applied the inductive and analytical methods that used as base to analyze and to give solution it. Also, the investigation types: descriptive, of field and bibliographical allowing to compile information, characteristics and local information. Besides, the technology is used as the observation, survey that allowed to visualize and to collect information by means of questionnaires and surveys….